1988
DOI: 10.1113/jphysiol.1988.sp016978
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory projections to the superior colliculus of the anaesthetized cat.

Abstract: SUMMARY1. Experiments in anaesthetized cats have shown that the superior colliculus receives deep afferent input from the forelimb and hindlimb, but not from the large superficial neck muscles.2. Neuronal activity in the superior colliculus is readily elicited by electrical stimulation of C2 and C3 cutaneous nerves. A significant proportion of neurones so activated have multiple receptive fields and some with no identifiable receptive fields in regions innervated by C2 and C3 nerves have receptive fields elsew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…This suggests that these SC neurons receive information about where the arm is going to be in this task (Werner et al, 1997;Stuphorn et al, 2000). Consistent with this observation, electrical stimulation of the forelimb and hindlimb muscle afferents in anesthetized monkeys resulted in firing of SC neurons at both short (20-50 msec) and long latencies (80-160 msec) (Abrahams and Rose, 1975;Abrahams et al, 1988). In behaving monkeys, SC neurons responding to the passive movement of the arm were much larger in number than those responding to cutaneous stimulation of the body surface (Nagy et al, 2006).…”
Section: Dsz Projections To the Midbrainsupporting
confidence: 56%
“…This suggests that these SC neurons receive information about where the arm is going to be in this task (Werner et al, 1997;Stuphorn et al, 2000). Consistent with this observation, electrical stimulation of the forelimb and hindlimb muscle afferents in anesthetized monkeys resulted in firing of SC neurons at both short (20-50 msec) and long latencies (80-160 msec) (Abrahams and Rose, 1975;Abrahams et al, 1988). In behaving monkeys, SC neurons responding to the passive movement of the arm were much larger in number than those responding to cutaneous stimulation of the body surface (Nagy et al, 2006).…”
Section: Dsz Projections To the Midbrainsupporting
confidence: 56%
“…The region is important for vision and hearing. Nevertheless, electrophysiological investigations have revealed the presence of cells with an apparently purely somatosensory input in the superior colliculus (Stein, Magalhaes-Castro & Kruger, 1976;Nagata & Kruger, 1979;Bitar, Saade & Banna, 1981;Abrahams, Clinton & Downey, 1988), which is a body notably belonging to the visual system. Likewise, purely somatosensory units have been found in the external nucleus of the inferior colliculus (Aitkin, Dickhaus, Schult & Zimmerman, 1978;Aitkin, Kenyon & Philpott, 1981;Tawil, Saade, Bitar & Jabbur, 1983), which is usually ranged with the auditory system.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are not controversial, and it is assumed that the convergence of the different types of sensory information in this region is important for the orienting reaction, which requires the co-ordination of teleceptive and haptic data. More specifically, it has been suggested that the tactile and proprioceptive input to the superior colliculus of the cat may be important for its use of the face for exploratory behaviour (Abrahams et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These observations call into question the traditional view of the SC as a structure where sensory and motor maps are in complete register (cf. Abrahams, Clinton & Downey, 1988).…”
Section: Introductionmentioning
confidence: 99%